PENINGKATAN KEPATUHAN PELAPORAN WAJIB PAJAK DENGAN MEDIA E-SPT - Pramitasari S.Ant S.Ak M.Ak, Dini Ayu (Fakultas Ekonomi Universitas Gresik, 2020)
ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â This research reviewed effort to increase tax payer reporting obedience through e-spt medium performed by socialization, monitoring and evaluation programs to embody tax payer reporting obedience and the e-spt implementation is matched with purpose of taxation administration reform that is effort to realize increasing tax payer reporting obedience and confidence on high tax administration. While from application side, e-spt implementation ruled about e-spt implementation. This study used interpretive qualitative method. Data used were derived from primary data through interview with fiscus and tax payer. The data were completed with related documents. Data analysis method was interpretive analysis according to Miles and Huberman: data collection, data reduction, data serving, and conclusion drawing. Result showed that effort on increasing tax payer reporting obedience with e-spt media as it s program of modernization in taxation administration. Of the research it is suggested to always use information technology in taxation activity in order to increase revenue from tax.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â